2022
DOI: 10.1002/anie.202204541
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate‐Enabled Nitrate Synthesis from Nitrogen Electrooxidation on a Rhodium Electrocatalyst

Abstract: The electrocatalytic nitrogen oxidation reaction (NOR) to generate nitrate is gaining increasing attention as an alternative approach to the conventional industrial manufacture. But, current progress in NOR is limited by the difficulties in activation and conversion of the strong N�N bond (941 kJ mol À 1 ). Herein, we designed to utilize sulfate to enhance NOR performance over an Rh electrocatalyst. After the addition of sulfate, the inert Rh nanoparticles exhibited superior NOR performance with a nitrate yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Interesting papers, mostly by Zhang's group [49][50][51][52], experimentally demonstrated that different materials can catalyze the NOR to HNO3 reaction. Their report on producing NO3 − on a Pt foil with a Faraday efficiency (FE) of ~ 1.23% at 2.19 VRHE (RHE is the abbreviation of reversible hydrogen electrode) was presented in 2019 [49], and the air was used as the N2 source.…”
Section: Electrochemical N Oxidationmentioning
confidence: 99%
“…Interesting papers, mostly by Zhang's group [49][50][51][52], experimentally demonstrated that different materials can catalyze the NOR to HNO3 reaction. Their report on producing NO3 − on a Pt foil with a Faraday efficiency (FE) of ~ 1.23% at 2.19 VRHE (RHE is the abbreviation of reversible hydrogen electrode) was presented in 2019 [49], and the air was used as the N2 source.…”
Section: Electrochemical N Oxidationmentioning
confidence: 99%
“…Ammonia, as a sustainable, carbon-free, high-energy chemical, lays the cornerstone for the manufacture of agricultural fertilizers, the provision of emerging hydrogen energy carriers, and the supply of clean fuels. Electrocatalytic nitrogen (N 2 ) reduction reaction (eNRR) powered by renewable electricity assembles the advantages of safety, low cost, modularity, and environmental friendliness to produce ammonia. However, such an attractive scheme encounters the bottleneck of inert N 2 molecules activation due to the high cleavage energy (941 kJ mol –1 ), leading to the hampered activity of ammonia synthesis at ambient conditions. Although numerous efforts including defect creation, interface construction, , and composition regulation have been devoted to overcoming these barriers, the insufficient electrons furnished by catalysts still impede the electrons approaching and subsequently breaking the NN bond.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibited sulfate formation and enhanced dithionate formation reaction without the participation of OH – , hence causing the negatively shifted electrode potentials. Besides, both the SOR products possess merits: sulfate can be converted to sulfuric acid by acidification for industrial use, and dithionate could be applied in the electroplating process and recycling of cathodes in spent Li-ion batteries. On the other hand, based on a previous study, SO 4 2– can be oxidized to S 2 O 8 2– under oxidation potential. However, S 2 O 8 2– ions were not detected by the IC and UV-iodometric methods (discussed in Supporting Information) under our experimental conditions (Figures S27 and S28).…”
Section: Resultsmentioning
confidence: 99%